2015
DOI: 10.1007/s00330-015-3686-3
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive diagnosis of hepatocellular carcinoma on gadoxetic acid-enhanced MRI: can hypointensity on the hepatobiliary phase be used as an alternative to washout?

Abstract: • Gadoxetic acid-enhanced MRI enhancement features can be used to diagnose HCC. • Washout should be determined on the PVP alone for high specificity. • Hypointensity on the TP or HBP increases sensitivity but lowers specificity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
105
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 52 publications
(56 reference statements)
6
105
1
Order By: Relevance
“…For these reasons, transitional phase hypointensity is not specific for HCC, even in combination with APHE, and it can be seen with hemangiomas, non-HCC malignancies, some dysplastic nodules, siderotic nodules, and other benign entities. A recent study confirmed that transitional phase hypointensity can lead to false-positive interpretations and hence lower specificity for the diagnosis of HCC (77). Given its lack of specificity, transitional phase hypointensity does not have the same diagnostic implication as "washout" and does not constitute a major feature in LI-RADS.…”
Section: Capsule Appearancementioning
confidence: 80%
See 1 more Smart Citation
“…For these reasons, transitional phase hypointensity is not specific for HCC, even in combination with APHE, and it can be seen with hemangiomas, non-HCC malignancies, some dysplastic nodules, siderotic nodules, and other benign entities. A recent study confirmed that transitional phase hypointensity can lead to false-positive interpretations and hence lower specificity for the diagnosis of HCC (77). Given its lack of specificity, transitional phase hypointensity does not have the same diagnostic implication as "washout" and does not constitute a major feature in LI-RADS.…”
Section: Capsule Appearancementioning
confidence: 80%
“…Although some studies have shown that transitional phase hypointensity is strongly predictive of HCCs (75)(76)(77), LI-RADS requires that "washout" after gadoxetate disodium injection be assessed in the portal venous phase, prior to the transitional or hepatobiliary phases. Due to rapid uptake of the agent by background hepatocytes, the liver is substantially enhanced in the transitional and hepatobiliary phases.…”
Section: Washout Appearancementioning
confidence: 99%
“…Furthermore, several studies have shown that the addition of hypointensity on the TP or HBP to the noninvasive diagnostic criteria may increase the diagnostic performance of Gd-EOB-MRI for small HCCs including subcentimeter lesions. However, there have been concerns regarding the lowering of specificity caused by difficulty in observing the enhancement pattern or signal intensity on T2-weighted imaging of subcentimeter sized, non-HCC lesions [27,29,30,47]. Moreover, it has been shown that a combination of Gd-EOB-MRI and diffusion-weighted imaging (DWI) provides even higher diagnostic sensitivity in the detection of small HCCs than Gd-EOB-MRI or DWI alone [48,49].…”
Section: Small Hccmentioning
confidence: 99%
“…These differences in the included phase(s) for assessing "washout" between guidelines may have been derived from the different preferences for either higher sensitivity or higher specificity of a Gd-EOB-MRI diagnosis of HCC. As an example, when hypointensity on the TP and/or HBP is used as an alternative to "washout", the sensitivity for the diagnosis of HCC is increased, which may be appropriate in situations in which a high detection rate is preferred [27][28][29][30] (fig. 1).…”
Section: Gadoxetic Acid-enhanced Mri In the Current Practice Guidelinmentioning
confidence: 99%
See 1 more Smart Citation